2019
DOI: 10.1016/j.toxrep.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple organ toxicity of Datura stramonium seed extracts

Abstract: HighlightsDatura stramonium seed extracts is toxic.Its toxicity affects the liver, kidney, heart and brain.Lipid peroxidation is one of the mechanisms of causing oxidative stress in target organs.Toxicity of Datura stramonium seed largely depends on solvent of extraction.Polarity and/or non-polarity of extraction solvent is linked to toxicity of Datura stramonium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
4
14
2
1
Order By: Relevance
“…Administration of ASEDS resulted in signi cant (p < 0.05) elevation of the antioxidant enzymes activities thereby restoring the normal antioxidant balance, thus, suggesting the ability of ASEDS to boost the rst line of defense against reactive oxygen species (ROS) generated from the bio-activation of cyclophosphamide. The results disagree with the report of Ogunmoyole et al [37] who demonstrated that the activities of SOD, CAT and GP X were depleted by administration of seed extract of D. stramonium L. regardless of the solvent used for the extraction. Cyclophosphamide induction also resulted in signi cant (p < 0.05) decrease in the concentrations of vitamins A, C, and E (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Administration of ASEDS resulted in signi cant (p < 0.05) elevation of the antioxidant enzymes activities thereby restoring the normal antioxidant balance, thus, suggesting the ability of ASEDS to boost the rst line of defense against reactive oxygen species (ROS) generated from the bio-activation of cyclophosphamide. The results disagree with the report of Ogunmoyole et al [37] who demonstrated that the activities of SOD, CAT and GP X were depleted by administration of seed extract of D. stramonium L. regardless of the solvent used for the extraction. Cyclophosphamide induction also resulted in signi cant (p < 0.05) decrease in the concentrations of vitamins A, C, and E (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…It was also observed that HDL-C concentration in each group was signi cantly higher than the corresponding LDL-C concentration indicating the extract possesses athero-protective capacity. The results corroborate the ndings of Ogunmoyole et al [37] who revealed that the HDL-cholesterol and LDL-cholesterol signi cantly increased in serum, liver and heart homogenates after administration of aqueous extract of D. stramonium seeds.…”
Section: Discussionsupporting
confidence: 91%
“…Some of these foreign compounds may cause injury to the liver resulting in the induction and release of liver enzymes and proteins in magnitude higher than the basal level [ 31 ]. Thus, significant alterations (particularly increase) in the levels and activities of serum liver function enzymes (ALT, AST, and ALP), particularly ALT, are indicative of injury on hepatocytes [ 31 ]. Serum proteins such as albumin are synthesized by the liver and the relative level could provide information on the synthetic capability of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, D. fastuosa was rendered safe up to a 2000 mg/kg body-weight dosage since it produced no sign of toxicity or mortality. Histological studies demonstrated the reduced weight of the organs, necrotic modifications in the liver accompanied by elevation of serum alkaline phosphatase, serum glutamic-oxaloacetic transaminase, and glutamyl pyruvic transaminase [65,66]. Moreover, due to its toxicity, D. stramonium should not be used in case of glaucoma, pyloric stenosis, paralytic ileus, tachycardia arrhythmias, enlarged prostate, and acute pulmonary edema [8].…”
Section: Toxicology Of Daturamentioning
confidence: 99%